International human rights regimes in Latin America: the commitment and compliance gap - Anaya-Muñoz, Alejandro (SocietàMutamentoPolitica, 2018)
Has the international human rights regime made a difference in practice? This article offers a preliminary approach to this question, focusing on Latin America. In particular, the article highlights the tensions between commitment and compliance with international human rights norms in the region. The article demonstrates that Latin-American countries have shown a strong commitment with these norms and with the organs of the universal and Inter-American human rights regimes. The article stresses, however, that high commitment has not been followed by a meaningful improvement in human rights conditions on the ground; therefore showing a clear gap between rights “in principle” and rights “in practice” in the region. The article concludes with an exploratory discussion on the possible causes for this decoupling and suggests future lines of research.